PENAMBAHAN DAGING IKAN GABUS (Ophicepallus strianus BLKR) DAN APLIKASI PEMBEKUAN PADA PEMBUATAN PEMPEK GLUTEN - Sugito, Sugito; Hayati, Ari (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2018)
The objectives of this research were to study the effects of freezing period of gluten and levels of gabus fillet fish addition on the characteristics of gluten pempek. This research was conducted at the Laboratory of Agricultural Product Chemistry, Department of Agricultural Technology, University of Sriwijaya, from July to October 2005. This research used completely randomized factorial design with two treatments and three replications. The treatments were freezing period (0, 6, and 12 hours) and levels of gabus fillet fish addition (0, 5, 10, and 15%). The observed parameters were content of water, ash, protein, carbohydrate and fat. The results showed that freezing time affected significantly on water content but not to the other parameters. Fillet fish addition level had significant effect on ash and fat, but had no significant effect on other parameters. The best treatment was gluten pempek using freezing time of 12 hours and 15% of fish addition level.